KEPATUHAN DAN KESADARAN WAJIB PAJAK UMKM DALAM MEMINIMALISIR KECURANGAN PAJAK DI WILAYAH JAKARTA DAN BEKASI - IGP Ratih Andaningsih; Wahyu Murti; Yolanda Yolanda (Universitas Trilogi, 2022)
The Author in conducting rsearch and community service activities wants to know the level of compliance and awareness of MSME taxpayers on tax obligations to pay taxes and report annual tax returns and reporting annual tax returns both manually and online on time.The purpose of this study is to better know and understand compliance and awareness to pay taxes and to report annual tax returns in reporting taxes owned.Through this qualitative descriptive study using content analysis with 15 informants on the results of long distance interviews from representatives of MSMEs in the Pondok Melati Sub District,Bekasi City,West Java and 10 key informants in Cipayung District,East Jakarta. Improvement of MSMEs business performance in terms of beingaware of carrying out tax obigations and being able to support the strengthening sector of state revenue for quality domestic MSMEs and fiscal taxes in a productive economic network in order to increase state income in the domestic tax sector. The limitation of the research is that it is limited to understanding and knowing the level of compliance and awareness of MSME taxpayers to pay taxes and reporting annual tax returns on time. The contribution of this research is the compliance and awareness of MSME taxpayers in paying taxes.Py their taxes and report their annual tax returns on time without any element of fraud.